1998
DOI: 10.1042/cs0940453
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Pattern of Pulmonary Flow Distribution following Unilateral Airway Occlusion in Sheep

Abstract: 1. Unilateral bronchial occlusion causes ipsilateral hypoxic pulmonary vasoconstriction, which shifts blood flow towards the other lung. We studied the time course of flow diversion following acute bronchial occlusion, and the temporal effect of the latter on blood gases and vertical distribution of blood flow within the two lungs. 2. Serial infusion of radioactive or fluorescent microspheres were given to each of seven adult standing sheep before, during occlusion of the left mainstem bronchus for up to 6 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Hypoxic pulmonary vasoconstriction (HPV) counteracts this hypoxemia, by increases pulmonary vascular resistance and diverting blood flow to the ventilated lung. Animal studies have shown that such flow diversion occurs within 30 s of unilateral bronchial occlusion, and blood flow to the occluded lung is approximately half that during double lung ventilation by two minutes 35 . If HPV is intact, shunt fraction during single-lung ventilation may be only 20%–30% of cardiac output, as opposed to the 50% that might be expected in its absence.…”
Section: Case I: Lung Resection In a Patient With Copdmentioning
confidence: 99%
“…Hypoxic pulmonary vasoconstriction (HPV) counteracts this hypoxemia, by increases pulmonary vascular resistance and diverting blood flow to the ventilated lung. Animal studies have shown that such flow diversion occurs within 30 s of unilateral bronchial occlusion, and blood flow to the occluded lung is approximately half that during double lung ventilation by two minutes 35 . If HPV is intact, shunt fraction during single-lung ventilation may be only 20%–30% of cardiac output, as opposed to the 50% that might be expected in its absence.…”
Section: Case I: Lung Resection In a Patient With Copdmentioning
confidence: 99%
“…Although the effect is larger with pulmonary artery occlusion, bronchial occlusion is much more practical to apply clinically. 14,20,21 …”
Section: Thermal Ablation In Lung Tissuementioning
confidence: 99%